S23 Accuracy of contrast enhanced MR lung perfusion compared to perfusion scintigraphy in diagnosing chronic thromboembolic pulmonary hypertension. (2nd December 2011) - Rajaram, S; Swift, A J; Capener, D; Hill, C; Davies, C; Elliot, R; Hurdman, J; Condliffe, R; Wild, J M; Kiely, D G
Abstract : Purpose: The purpose of our study was to assess the diagnostic accuracy and reliability of contrast enhanced MR lung perfusion compared to perfusion scintigraphy in patients with CTEPH. Methods and Materials: Retrospective analysis of patients investigated for CTEPH who had MR lung perfusion, perfusion scintigraphy and CTPA performed within a time interval of 5 days. The MR images were acquired using a time resolved 3D spoiled gradient echo sequence. The sequence parameters: TE 1.1 ms, TR 2.5 ms, flip angle of 30°, FOV=48 cm 2, slice thickness of 5 mm, average of 32 slices and frame rate was 2 acquisitions per second. This was a breathhold sequence obtained after 0.05 ml/kg of Gadovist injection at 5 ml/s followed by a 20 ml saline flush. The subtraction images and positive enhancement dataset were analysed in the coronal plane. Four static views perfusion scintigraphy views were obtained. Final diagnosis of CTEPH or non-CTEPH was made at a multidisciplinary meeting following detailed multi-modality assessment. Results: 27 patients had a diagnosis of CTEPH and 55 patients were diagnosed as non-CTEPH. In the CTEPH group, MRI lung perfusion diagnosed 26 patients as CTEPH and 1 patient with distal surgically inaccessible disease as non-CTEPH. In the non-CTEPH group, four patients were diagnosed as CTEPH and 48 patients were identified as non-CTEPH and three MRI were considered non-diagnostic. MR lung perfusion was not performed in 11 patients due to impaired renal function or patient unable to tolerate breathhold. None of the surgically accessible disease was missed with either modality. The MR lung perfusion had a sensitivity of 96%, specificity of 92%, PPV of 87%, NPV of 98% and accuracy of 94% for diagnosing CTEPH. Perfusion scintigraphy had a sensitivity of 93%, specificity of 90%, PPV of 83%, NPV of 96% and accuracy of 91%. Conclusion: Our results show that MR lung perfusion compared to 4-view static perfusion scintigraphy has an overall higher accuracy compared to perfusion scintigraphy and has a role in assessment of patients with suspected CTEPH.